Fabrikasi Kawat Resistansi Nol Berbahan MgB2/Stainless Steel dengan Variasi Reduksi Ukuran melalui Pengerolan Dingin terhadap Karakteristik Mekanik dan Struktur Mikro - Satrio Herbirowo; Andika Widya Pramono (Sekolah Tinggi Teknik PLN, 2021)
Magnesium Diboride (MgB2) is a high potential material for medical and electrical applications with zero resistance and high efficiency. The raw materials of Mg powder with a purity of 98% and B amorphous with a purity of 95%, were mixed with a ratio of 1:2, ground for 2 hours using an agate mortar, and subsequently compacted and inserted into stainelss steel (SS) tube by powder-in-tube (PIT). The SS tube was previously annealed at 900°C for 1 hour. The sintering process was carried out using a muffle furnace at a temperature of 800°C for 1 hour, followed by cold wire rolling with gradual reduction. The samples were characterized for their mechanical properties using Vickers microhardness tester and ultimate tensile test machine. Surface morphologies of samples were observed using optical microscope and SEM-EDAX Superconducting properties were measured with the cryogenic resistance measurement. The highest hardness value of 377,2 HV was achieved at a 60% size reduction along with the tensile strength of 1381 KN/mm. The results of the morphological observation showed homogeneous deformation without any cracks, with the the grain shape tended to be crystalline. The superconductivity test showed the phenomenon of zero resistance at a critical temperature of 39.55K at a 40% reduction in MgB2 wire